2021
DOI: 10.3389/fphar.2021.648969
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin-3,3′-Digallate Promotes the Formation of Osteoblasts Under Inflammatory Environment and Increases the Bone Mass of Ovariectomized Mice

Abstract: Postmenopausal osteoporosis is a disease of bone mass reduction and structural changes due to estrogen deficiency, which can eventually lead to increased pain and fracture risk. Chronic inflammatory microenvironment leading to the decreased activation of osteoblasts and inhibition of bone formation is an important pathological factor that leads to osteoporosis. Theaflavin-3,3′-digallate (TFDG) is an extract of black tea, which has potential anti-inflammatory and antiviral effects. In our study, we found that T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Theaflavin-3,3′-digallate activates several signaling pathways, including the tumor necrosis factor-α (TNF-α)-inhibited mitogen-activated protein kinase (MAPK), Wnt/βcatenin, and BMP/Smad pathways. This mechanism ultimately promotes the transcription of osteogenesis-associated factors such as RUNX2 and Osterix, leading to osteoblast differentiation and maturation (46). Furthermore, various tea extracts and tea polyphenols inhibit osteoclast formation, with EGCG being the most effective (47)(48)(49)(50)(51).…”
Section: Studies Of Tea Treating Osteoporosismentioning
confidence: 99%
“…Theaflavin-3,3′-digallate activates several signaling pathways, including the tumor necrosis factor-α (TNF-α)-inhibited mitogen-activated protein kinase (MAPK), Wnt/βcatenin, and BMP/Smad pathways. This mechanism ultimately promotes the transcription of osteogenesis-associated factors such as RUNX2 and Osterix, leading to osteoblast differentiation and maturation (46). Furthermore, various tea extracts and tea polyphenols inhibit osteoclast formation, with EGCG being the most effective (47)(48)(49)(50)(51).…”
Section: Studies Of Tea Treating Osteoporosismentioning
confidence: 99%
“…In vitro experiments have shown that TFDG can promote the formation of osteoblasts in an inflammatory environment and enhance their mineralization ability. During this process, TFDG activates the MAPK, Wnt/beta-Catenin, and BMP/Smad signaling pathways ( Ge et al, 2021 ). Hou found that TF3 can effectively inhibit the expression of pro-inflammatory cytokines in ovariectomized mice, promote polarization of M1 macrophages to M2 macrophages, reduce inflammatory response, promote bone formation, and effectively reduce bone loss.…”
Section: Catechins Participate In Regulating Bone Massmentioning
confidence: 99%
“…Furthermore, green tea extract in the condition of oxidative stress led to the increased expression of osteocalcin and collagen 1α1 during osteoblast differentiation [148]. In addition to green tea, black tea polyphenols, particularly theaflavin-3,3 -digallate (TFDG), were recently found through in vitro and in vivo studies [149][150][151] to display strong antioxidant and anti-inflammatory activities by reducing the levels of nitric oxide precursor, malondialdehyde (MDA), lipid peroxidation, and SOD. Furthermore, the same studies showed that serum levels of TNFα, IL-6, and RANKL were reduced, along with tartrate-resistant acid phosphatase activity, the osteoclast enzyme.…”
Section: Flavonoidsmentioning
confidence: 99%